Abrasive composition for plastic lens
By using an abrasive composition containing alumina, water-soluble polymer compound and water, the problems of low polishing efficiency and rough surface of plastic lenses in the prior art are solved, and the effect of efficient polishing and glossy surface is achieved.
Patent Information
- Application Number
- CN202380070437.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-20
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-29
AI Technical Summary
The conventional abrasive composition for plastic lenses is difficult to achieve high abrasive efficiency and glossy surface when grinding low-refractive and high-refractive index plastic lenses.
The abrasive composition containing alumina, water-soluble polymer compounds (oxazoline-based polymers with specific chemical structures) and water is used to increase the grinding speed and achieve a glossy surface through the combination of these components.
The grinding speed of the plastic lens is significantly improved, high grinding efficiency is achieved, and excellent effect of processing into a glossy surface.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a polishing agent composition for plastic lenses. Background Art
[0002] In recent years, plastic lenses made of resin raw materials have been used as optical lenses instead of glass lenses. The reason is that plastic lenses have advantages such as being lightweight, not easy to break, and easy to process and shape compared to glass lenses. This plastic lens is widely used in the optical field, and is particularly used as a lens for glasses because of the above advantages.
[0003] As the substrate for plastic lenses, acrylic resin, polycarbonate, cycloolefin polymer, cycloolefin copolymer, and thiourethane resin can be cited. Acrylic resin (PMMA) has excellent transparency and weather resistance, good mechanical strength and high surface hardness, so it is also called organic glass. Compared with glass, it allows light to pass through and has a lower refractive index, so it is widely used as a raw material for optical lenses. However, it has the disadvantages of high water absorption, change in refractive index due to water absorption, and low heat resistance.
[0004] Furthermore, polycarbonate is a type of engineering plastic with high impact resistance, has the same degree of transparency as glass, and has a high transparency second only to acrylic resin. In addition, although polycarbonate is excellent in dimensional stability, it has a disadvantage of large birefringence. For example, a polycarbonate-based allyl diglycol carbonate polymer is known as CR-39 (registered trademark) (manufactured by Pittsburgh Plate Glass Company (PPG Industries)).
[0005] Cycloolefin polymer is a cyclic olefin polymer obtained by ring-opening polymerization of cyclopentadiene monomer and stabilizing it by hydrogenation. It has the same transparency as acrylic resin and has the lowest water absorption among plastics. It has excellent dimensional stability even under high humidity and almost no warping or deformation of molded products, so it is suitable for precision molding.
[0006] Cyclic olefin copolymer is a cyclic olefin copolymer, which is a polymer obtained by addition polymerization of two monomers, norbornene and ethylene units. It has high rigidity, high transparency (transparency equivalent to that of acrylic resin), and high optical properties (high transparency, low birefringence), and has excellent properties as an optical component.
[0007] Thiourethane resin is a polymer obtained by reacting a polyisocyanate compound with a polythiol composition, and has a high refractive index and excellent impact resistance, and is therefore widely used for high refractive index plastic lenses. For example, MR-10 (registered trademark) (manufactured by Mitsui Chemicals, Inc.) is known.
[0008] Various plastic lens abrasive compositions used for grinding these plastic lens substrates are well known to those skilled in the art. These known abrasive compositions are usually composed of abrasive particles dispersed in water and / or other liquids. As such abrasive particles, for example, cerium oxide, aluminum oxide, zirconium oxide, tin oxide, silicon dioxide, and titanium oxide are known.
[0009] Here, the alumina slurry is used as an abrasive composition for a plastic lens for grinding the above-mentioned plastic lens substrate. In the case of an abrasive composition for a plastic lens containing only alumina abrasive particles dispersed in water, if used for grinding a plastic lens substrate, it will show an acceptable surface quality, but on the other hand, it may sometimes show an unacceptably low grinding efficiency. Although such a slurry composition can improve the grinding efficiency by using relatively large alumina particles, it will bring unacceptable surface quality, that is, scratches, dents, orange peel-like bumps (orange peel texture, orange peel) or similar defects.
[0010] For example, Patent Document 1 (U.S. Patent No. 4,225,349) shows that a plastic lens polishing composition containing calcined alumina (alumina particles) and an aluminum salt polishing accelerator such as aluminum nitrate dispersed in deionized water promotes polishing of a CR-39 substrate material without impairing the surface quality.
[0011] On the other hand, Patent Document 2 (Japanese Patent Publication No. 2008-537704) proposes to obtain high polishing efficiency by using an alumina-based polishing composition to which a pyrrolidone compound or polyvinyl caprolactam is added, but sufficient polishing efficiency has not yet been achieved.
[0012] Furthermore, Patent Document 3 (Japanese Patent Publication No. 2018-533071) proposes obtaining high polishing efficiency by using an alumina-based polishing composition to which a small amount of a tertiary amide-containing compound is added, but similarly, sufficient polishing efficiency is not achieved.
[0013] Prior art literature Patent Literature Patent Document 1: U.S. Patent No. 4,225,349 Patent Document 2: Japanese Patent Application No. 2008-537704 Patent Document 3: Japanese Patent Application No. 2018-533071 Summary of the invention
[0014] Technical problem to be solved by the invention The known plastic lens abrasive composition used for polishing low refractive index substrates such as CR-39 cannot provide sufficient polishing efficiency even in the presence of a polishing accelerator such as aluminum nitrate. Even for plastic lens substrates such as thiourethane resins having a higher refractive index (such as MR-10), the development of a plastic lens abrasive composition having high polishing efficiency is also expected.
[0015] Therefore, in view of the above-mentioned actual situation, the technical object of the present invention is to provide a polishing agent composition for plastic lenses which can exhibit high polishing efficiency for polishing a plastic lens substrate such as polycarbonate or thiourethane resin.
[0016] Technical solutions for solving technical problems The inventors of the present application conducted intensive studies to solve the above-mentioned technical problems and found that by using the following plastic lens polishing composition, a glossy surface shape with high polishing efficiency can be obtained for both low-refractive-index and high-refractive-index plastic lens substrates.
[0017] [1] A polishing agent composition for a plastic lens, comprising aluminum oxide, a water-soluble polymer compound and water, wherein the water-soluble polymer compound is an oxazoline group-containing water-soluble polymer compound in which an oxazoline group represented by the following chemical formula 1 is bonded to the main chain of the polymer.
[0018] [Chemical formula 1]
[0019] (In Chemical Formula 1, R1, R2, R3, and R4 are each any one of H, CH3, and CH2CH3.) [2] The polishing agent composition for a plastic lens according to [1], wherein the oxazoline group-containing water-soluble polymer compound contains a structural unit derived from an acrylic monomer and a structural unit derived from an oxazoline group-containing monomer as essential structural units.
[0020] [3] The polishing compound for a plastic lens according to [2], wherein the acrylic monomer is at least one selected from acrylamide, methacrylamide, acrylic acid, acrylic acid salts, acrylic acid esters, methacrylic acid, methacrylic acid salts, and methacrylic acid esters.
[0021] [4] The polishing agent composition for a plastic lens according to [2], wherein the oxazoline group-containing monomer is at least one selected from 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline and 2-isopropenyl-5-ethyl-2-oxazoline.
[0022] [5] The polishing compound for a plastic lens according to [1], wherein the oxazoline group-containing water-soluble polymer compound is obtained by graft polymerization of an addition-polymerizable oxazoline and a polyether.
[0023] [6] The polishing compound for a plastic lens according to [1], wherein the oxazoline group-containing water-soluble polymer compound is obtained by reacting an amino alcohol with a polymer having a carboxyl group and / or an ester group.
[0024] [7] The polishing compound for a plastic lens according to any one of [1] to [6], further comprising a dispersant.
[0025] [8] The polishing compound for a plastic lens according to any one of [1] to [6], wherein the pH value (25° C.) of the polishing compound for a plastic lens is 1.0 to 10.0.
[0026] Effects of the Invention The polishing agent composition for plastic lenses of the present invention is characterized in that it contains aluminum oxide, a water-soluble polymer compound and water, and in particular, the water-soluble polymer compound is a water-soluble polymer compound containing an oxazoline group. By being used for polishing plastic lenses, the polishing speed can be increased, high polishing efficiency can be achieved, and the excellent effect of processing the polished plastic lens into a glossy surface can be achieved. DETAILED DESCRIPTION
[0027] The present invention is not limited to the following embodiments, and can be changed, modified, and improved without departing from the gist of the invention.
[0028] 1. Abrasive composition for plastic lens The abrasive composition for plastic lens of the present invention (hereinafter referred to as "abrasive composition") is characterized by containing aluminum oxide, a water-soluble polymer compound and water. Furthermore, a dispersant may also be preferably contained. Hereinafter, each structure of the abrasive composition of one embodiment of the present invention is described in detail.
[0029] 1.1 Alumina Alumina used in the polishing compound of this embodiment can be used α -alumina, intermediate alumina, and α -Any mixture of aluminum oxide and intermediate aluminum oxide. In addition, as intermediate aluminum oxide, for example, c - Alumina, d - Alumina and i -Alumina, etc.
[0030] In particular, in the polishing of a plastic lens substrate, it is preferable to use a α -Alumina.
[0031] Examples of raw materials for producing alumina used in the polishing composition of the present embodiment include gibbsite: Al2O3.3H2O, boehmite: Al2O3.H2O, pseudo-boehmite: Al2O3.nH2O (n=1 to 2), etc. These alumina raw materials can be prepared, for example, by the following method.
[0032] ·Gibsmelt: Al2O3·3H2O The bauxite can be obtained by dissolving bauxite in a hot solution of sodium hydroxide, removing impurities by filtration, cooling the obtained solution, and drying the obtained precipitate.
[0033] ·Boehmite: Al2O3·H2O It can be obtained by hydrolyzing aluminum alkoxide: Al(OR)3 obtained by the reaction of metallic aluminum and alcohol.
[0034] ·Pseudo-boehmite: Al2O3·nH2O (n=1~2) It can be obtained by treating gibbsite with water vapor in an alkaline atmosphere.
[0035] Furthermore, by sintering the above-mentioned alumina raw material, α - Aluminium oxide, or c - Alumina, d - Alumina, i - Intermediate aluminum oxides such as alumina.
[0036] Here, the average particle size (D50) of the aluminum oxide used is preferably 0.1 to 10.0 m m, more preferably 0.1 to 5.0 m m is more preferably 0.2 to 2.0 m m.
[0037] In addition, the concentration of aluminum oxide in the polishing compound of the present embodiment is preferably 1 to 50% by mass, more preferably 2 to 45% by mass, and still more preferably 3 to 40% by mass. If the concentration of aluminum oxide is less than 1% by mass, a sufficient polishing rate cannot be obtained, while if the concentration of aluminum oxide is more than 50% by mass, no further improvement in the polishing rate can be confirmed, which is inappropriate in terms of economy.
[0038] 1.2 Water-soluble polymer compounds The water-soluble polymer compound used in the polishing compound of the present embodiment has the following characteristics: it is a water-soluble polymer compound containing an oxazoline group, in which an oxazoline group of the following chemical formula 1 is bonded to the main chain of the polymer. In other words, a water-soluble polymer compound containing an oxazoline group having a five-membered ring structure having a carbon-nitrogen double bond is used.
[0039] [Chemical formula 1]
[0040] In the above Chemical Formula 1, R1, R2, R3, and R4 are each any one of H, CH3, and CH2CH3.
[0041] Here, the water-soluble polymer compound containing oxazoline group can be obtained by various methods known in the past. For example, by free radical copolymerization of monomers containing oxazoline group and other monomers, water-soluble polymer compound containing oxazoline group can be obtained. And then, it is also possible to obtain water-soluble polymer compound containing oxazoline group by graft polymerization of monomers containing oxazoline group and existing polymers such as polyethers and acrylic polymers. For example, it is also possible to use the structural unit from acrylic monomers and the structural unit from the monomer containing oxazoline group as necessary structural units.
[0042] Furthermore, an oxazoline group-containing water-soluble polymer compound can also be obtained by reacting an amino alcohol with a polymer having a carboxyl group and / or an ester group.
[0043] In addition, the oxazoline polymer obtained by ring-opening the oxazoline compound by cationic polymerization is a polymer without the above-mentioned carbon-nitrogen double bond, and is different from the water-soluble polymer compound containing an oxazoline group having a five-membered ring structure with a carbon-nitrogen double bond used in the polishing compound of the present invention. The above three methods for obtaining the water-soluble polymer compound containing an oxazoline group are specifically described below.
[0044] 1.2.1 Method for obtaining a water-soluble polymer compound containing an oxazoline group by free radical copolymerization of an acrylic monomer and an addition-polymerizable oxazoline Specific examples of the addition polymerizable oxazoline include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
[0045] On the other hand, specific examples of acrylic monomers include acrylamide, methacrylamide, acrylic acid, acrylates, acrylate esters, methacrylic acid, methacrylates, and methacrylate esters. More specifically, acrylamide, methacrylamide, acrylic acid, sodium acrylate, potassium acrylate, ammonium acrylate, methyl acrylate, ethyl acrylate, methacrylic acid, sodium methacrylate, potassium methacrylate, ammonium methacrylate, methyl methacrylate, and ethyl methacrylate.
[0046] When the above-mentioned monomer components are subjected to free radical polymerization, a polymerization initiator can be used. Examples of the polymerization initiator include azo compounds such as azobisisobutyronitrile, 2,2-azobis(2-methylbutyronitrile), and 2,2-azobis(2-diaminopropane) hydrochloride; persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate; and peroxides such as hydrogen peroxide, benzoyl peroxide, p-chlorobenzoyl peroxide, and ammonium peroxide, without particular limitation.
[0047] Furthermore, as a polymerization method, solution polymerization, bulk polymerization or suspension polymerization can be used. In particular, since the oxazoline group-containing polymer is a water-soluble high molecular compound, solution polymerization using a mixed solvent of water and an organic solvent is preferred. Furthermore, as preferred organic solvents, methanol, ethanol, n-propanol, isopropanol, methoxyethanol, ethoxyethanol and methoxypropanol can be mentioned.
[0048] Here, the polymerization temperature when polymerizing the monomer components is usually preferably 20 to 150°C, more preferably 60 to 95°C.
[0049] The atmosphere during polymerization of the monomer components is not particularly limited, but is preferably an inert gas such as nitrogen from the viewpoint of improving the efficiency of the polymerization initiator.
[0050] 1.2.2 Method for obtaining a water-soluble polymer compound containing an oxazoline group by graft polymerization of an addition-polymerizable oxazoline with a polyether Here, the polyether forming the main chain of the graft polymer may be a conventional polyether having a structural unit derived from an alkylene oxide, and from the viewpoint of water solubility of the graft polymer, it is preferred that ethylene oxide be included as an essential component as the alkylene oxide. The number average molecular weight of the polyether is preferably in the range of 200 to 100,000. When it is less than 200, the molecular weight of the obtained graft polymer becomes low, and when it exceeds 100,000, the viscosity becomes high, and handling during graft polymerization may become difficult.
[0051] Examples of the addition polymerizable oxazoline include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
[0052] In the graft polymerization, it is preferred to use a polymerization initiator, and as the polymerization initiator, it is preferred to use an organic peroxide. Examples of the organic peroxide include methyl ethyl ketone peroxide, cyclohexanone peroxide, tert-butyl hydroperoxide, and cumene hydroperoxide.
[0053] When the graft polymerization is carried out using a reaction solvent, isobutyl alcohol, n-butyl alcohol, tert-butyl alcohol, ethylene glycol, diethylene glycol, and the like can be used as the reaction solvent.
[0054] The polymerization temperature during graft polymerization is not particularly limited, but is preferably 20 to 160° C. If the temperature is lower than 20° C., graft polymerization is difficult to proceed, while if the temperature exceeds 160° C., thermal decomposition of the polyether chain and the resulting graft polymer may occur.
[0055] 1.2.3 Method for obtaining a water-soluble polymer compound containing an oxazoline group by reacting an amino alcohol with a polymer having a carboxyl group and / or an ester group Specific examples of polymers having carboxyl groups and / or ester groups include acrylic acid polymers, methacrylic acid polymers, acrylic acid ester polymers, methacrylic acid ester polymers, and copolymers thereof. In addition, other carboxyl group-containing monomers include dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid.
[0056] Examples of the acrylic acid ester include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, and 2-ethylhexyl acrylate.
[0057] Examples of the methacrylate include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate.
[0058] Specific examples of the amino alcohol include ethanolamine, 2-amino-1-propanol, 3-amino-2-propanol, 3-amino-2-butanol, 2-amino-2-phenyl-ethanol, and 2-amino-3-phenyl-butanol.
[0059] The reaction of the polymer having a carboxyl group and / or an ester group with the amino alcohol may be carried out without a catalyst, but in order to improve the reaction yield, a transition metal compound (eg, a zinc compound, a cadmium compound, etc.) may be used as a catalyst.
[0060] The reaction conditions can adopt any appropriate conditions. For example, it can be carried out in any appropriate solvent. Alternatively, it is also possible to put a polymer having a carboxyl group and / or an ester group into a twin-screw extruder to melt the polymer, add a solution of amino alcohol and a transition metal compound, and react the carboxyl group and / or the ester group with aminoethanol in the absence of a solvent.
[0061] Examples of the solvent include aromatic solvents such as toluene, xylene, and chlorobenzene; ester solvents such as butyl acetate and ethyl acetate; and ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0062] The reaction temperature of the above reaction is preferably 80 to 180° C., more preferably 100 to 175° C., and most preferably 150 to 170° C. The reaction temperature is set in consideration of the type and amount of the solvent used.
[0063] The ratio of the structural unit derived from the monomer containing an oxazoline group in the water-soluble polymer containing an oxazoline group is defined as the amount of oxazoline groups (mmol / g·solid content), and the preferred range of the amount of oxazoline groups is 0.1 to 20.0 mmol / g·solid content, and more preferably 0.2 to 10.0 mmol / g·solid content. Here, the amount of oxazoline groups (mmol / g·solid content) represents the number of mmol of the structural unit derived from the monomer containing an oxazoline group per 1 g of the water-soluble polymer containing an oxazoline group. It should be noted that the method for calculating the amount of oxazoline groups is a theoretical value assuming that the reaction rate of the input monomer is 100%.
[0064] The weight average molecular weight of the oxazoline group-containing water-soluble polymer compound is generally in the range of 1000 to 1000000, and preferably in the range of 5000 to 500000. The weight average molecular weight of the oxazoline group-containing water-soluble polymer compound can be determined by gel permeation chromatography (GPC).
[0065] The content of the oxazoline group-containing water-soluble polymer compound in the polishing composition is usually 0.001 to 5.0% by mass, preferably 0.01 to 3.0% by mass.
[0066] 1.3 Dispersants The polishing agent composition of the present invention may contain a dispersant as required. The dispersant is at least one selected from alumina sol, cellulose and condensed phosphate.
[0067] Since it is necessary to prevent the aluminum oxide particles in the polishing composition from settling over time or during standing, and from the perspective of handling the polishing composition, even if the aluminum oxide particles settle during long-term storage, it is desired to easily redisperse the aluminum oxide particles. Therefore, a dispersant is added to the polishing composition.
[0068] Alumina sol is a colloidally dispersed aluminum hydroxide or hydrated aluminum oxide in an aqueous solution. Examples of hydrated aluminum oxide include boehmite, pseudo-boehmite, diaspore, gibbsite, and bayerite.
[0069] As the alumina sol in which aluminum hydroxide is dispersed in an aqueous solution in a colloidal state, it is preferred to use a sol product of an aluminum salt. The sol product of an aluminum salt is obtained by reacting various aluminum salts with a compound that easily reacts with water to generate a hydroxyl group. Alternatively, it can be obtained by reacting various aluminum salts with a compound containing a hydroxyl group.
[0070] As various aluminum salts used, aluminum sulfate, aluminum chloride and aluminum nitrate can be mentioned. As compounds that easily react with water to generate hydroxyl groups, ammonia, alkylamines, amine chelate compounds, aminocarboxylic acids, aminocarboxylic acid chelate compounds and aminophosphonic acid chelate compounds can be mentioned. As compounds containing hydroxyl groups used, sodium hydroxide and potassium hydroxide can be mentioned.
[0071] As the alumina sol in which hydrated aluminum oxide is dispersed in an aqueous solution in a colloidal state, boehmite sol is preferably used. Boehmite sol is obtained by allowing boehmite or pseudo-boehmite to coexist with various aluminum salts, inorganic acids, organic acids, etc. As various aluminum salts used, aluminum sulfate, aluminum chloride, and aluminum nitrate can be mentioned. As inorganic acids used, nitric acid and hydrochloric acid can be mentioned. As organic acids used, acetic acid and gluconic acid can be mentioned.
[0072] Examples of the celluloses include cellulose, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
[0073] Examples of the condensed phosphate include sodium hexametaphosphate, sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, acidic sodium metaphosphate, and acidic sodium pyrophosphate. Among these dispersants, alumina sol is preferably used.
[0074] The content of the dispersant in the polishing agent composition is preferably 0.01 to 5.00 mass %, and more preferably 0.02 to 2.00 mass %. When it is less than 0.01 mass %, the dispersion effect of the aluminum oxide particles is reduced. When it exceeds 5 mass %, there is a concern that the viscosity of the polishing agent composition increases and the fluidity of the polishing agent composition decreases.
[0075] 1.4 Water The water used in the present invention is preferably water from which impurities such as distilled water and ion exchange water are removed. Water has the function of controlling the fluidity of the abrasive composition, so its content can be appropriately determined according to the target grinding characteristics such as the grinding speed. For example, the water content is preferably 40 to 90% by mass. If the water content is less than 40% by mass of the abrasive composition, the viscosity of the abrasive sometimes increases, impairing fluidity. On the other hand, if the water content exceeds 90% by mass, the abrasive concentration sometimes decreases, and a sufficient grinding speed cannot be obtained.
[0076] 2. Physical properties The pH (25°C) of the polishing compound of the present invention is preferably in the range of 1.0 to 10.0, and more preferably in the range of 2.0 to 7.0. If the pH (25°C) is less than 1.0, there is a concern that the polishing machine, piping, etc. may be corroded. If the pH (25°C) exceeds 10.0, there is a concern that the surface roughness of the polished plastic lens may deteriorate. As described above, in order to adjust the pH of the polishing compound to a preferred range, the polishing compound of the present embodiment may use a pH adjuster such as an acid, an alkali, and a salt thereof.
[0077] 3. Grinding method of plastic lens The polishing of plastic lenses is usually carried out using a grinder for curved surface polishing designed to perform polishing consistent with the curvature of the lens surface, but the polishing performance of the abrasive composition can also be evaluated using a grinder for plane polishing of a flat plastic lens raw material. Therefore, the polishing performance evaluation of the abrasive composition of the present invention is carried out as follows using a grinder for plane polishing.
[0078] A prescribed amount of abrasive composition is put into a supply container provided in a grinder. Then, the abrasive composition is dripped and supplied to a grinding pad attached to a platform of the grinder from the supply container via a nozzle and a tube, and the grinding surface of the grinding object is pressed against the grinding pad surface, and the platform is rotated at a prescribed rotation speed, thereby grinding the surface of the grinding object. The grinding pad can use any of suede type, non-woven fabric type and other types. In addition, as the surface shape of the grinding pad, a grooved, grooveless, or arbitrary grinding pad can be used.
[0079] Example Hereinafter, the polishing agent composition of the present invention will be further described in detail based on the following examples, but the present invention is not limited to these examples. In addition, in the present invention, in addition to the following examples, various changes and improvements can be applied based on the knowledge of those skilled in the art without departing from the scope of the present invention.
[0080] The polishing compositions prepared as Examples 1 to 13 and Comparative Examples 1 to 9 respectively contain the materials described in Table 1 shown below in the contents described in Table 1. Furthermore, the results of various polishing tests (details will be described later) using the polishing compositions of Examples 1 to 13 and Comparative Examples 1 to 9 are shown in Tables 2 and 3.
[0081] Here, Table 2 shows the polishing test results when a low-refractive-index substrate (CR-39) is used as the polishing target, while Table 3 shows the test results when a high-refractive-index substrate (MR-10) is used as the polishing target.
[0082] Here, the oxazoline group-containing water-soluble polymer compounds used in the examples were the following two types.
[0083] ·EPOCROS WS-500 (manufactured by Nippon Shokubai Co., Ltd., polymer main chain = acrylic acid (Japanese original name: "アクリル"), R1 to R4 in the chemical formula 1 of the oxazoline group are all H, oxazoline group content = 4.5 mmol / g·solid content, weight average molecular weight = 70,000) ·EPOCROS WS-700 (manufactured by Nippon Shokubai Co., Ltd., polymer main chain = acrylic acid, R1 to R4 in the chemical formula 1 of the oxazoline group are all H, oxazoline group content = 4.5 mmol / g·solid content, weight average molecular weight = 40,000) The polyvinyl alcohol used in Comparative Examples is as follows.
[0084] JP-18 (manufactured by Japan Vam & Poval Co., Ltd., saponification degree = 88%, polymerization degree = 1800, R1 to R4 in the chemical formula 1 of the oxazoline group are all H) [Table 1]
[0085] 4. Preparation method of abrasive composition 4.1 Preparation of the Abrasive Composition of Example 1 The commercially available α - Alumina (average particle size (D50) = 1.7 mm), commercially available alumina sol, aluminum nitrate, and EPOCROS WS-500 (weight average molecular weight = 70,000) as a water-soluble polymer compound were diluted with pure water to a concentration as shown in Table 1, stirred and mixed, and homogenized, and the resulting substance was used as the polishing composition of Example 1 for a polishing test. The results of the polishing test using the polishing composition of Example 1 are shown in Table 2.
[0086] 4.2 Preparation of the Abrasive Composition of Example 2 The polishing composition of Example 2 was prepared in the same manner as in Example 1 except that the content of EPOCROS WS-500 used in the preparation of the polishing composition of Example 1 was changed to the amount described in Table 1. The results of the polishing test using the polishing composition of Example 2 are shown in Table 2.
[0087] 4.3 Preparation of the Abrasive Composition of Example 3 The polishing composition of Example 3 was prepared in the same manner as in Example 1 except that the water-soluble polymer compound was changed to EPOCROS WS-700 (weight average molecular weight = 40,000) and used in the polishing test. The results of the polishing test using the polishing composition of Example 3 are shown in Table 2.
[0088] 4.4 Preparation of the Abrasive Composition of Example 4 The polishing composition of Example 4 was prepared in the same manner as in Example 3 except that the content of EPOCROS WS-700 used in the preparation of the polishing composition of Example 3 was changed to the amount described in Table 1. The results of the polishing test using the polishing composition of Example 4 are shown in Table 2.
[0089] 4.5 Preparation of the Abrasive Composition of Example 5 The aluminum oxide used in the preparation of the polishing compound of Example 2 was changed to α - Alumina (average particle size (D50) = 0.7 m m), the polishing test was performed in the same manner as in Example 2, and the polishing composition was used as Example 5. The results of the polishing test using the polishing composition of Example 5 are shown in Table 2.
[0090] 4.6 Preparation of the Abrasive Composition of Example 6 The polishing composition of Example 2 was prepared in the same manner as in Example 2 except that 0.1 mass % of citric acid was added so that the pH (25° C.) became 2.0, and was used in the polishing test as the polishing composition of Example 6. The results of the polishing test using the polishing composition of Example 6 are shown in Table 2.
[0091] 4.7 Preparation of the Abrasive Composition of Example 7 The polishing composition of Example 7 was prepared in the same manner as in Example 2 except that aluminum nitrate was not used and the pH (25° C.) was adjusted to 7.5. The results of the polishing test using the polishing composition of Example 7 are shown in Table 2.
[0092] 4.8 Preparation of the Abrasive Composition of Example 8 The polishing composition of Example 2 was prepared in the same manner as in Example 2 except that sodium hydroxide was added so that the pH (25° C.) became 10.0, and was used in the polishing test as the polishing composition of Example 8. The results of the polishing test using the polishing composition of Example 8 are shown in Table 2.
[0093] 4.9 Preparation of the Abrasive Composition of Example 9 A polishing agent composition was prepared in the same manner as in Example 1, and used in the polishing test of Example 9. Table 3 shows the results of the polishing test using the polishing agent composition of Example 9.
[0094] 4.10 Preparation of the Abrasive Composition of Example 10 A polishing agent composition was prepared in the same manner as in Example 2, and used in the polishing test of Example 10. Table 3 shows the results of the polishing test using the polishing agent composition of Example 10.
[0095] 4.11 Preparation of the Abrasive Composition of Example 11 A polishing agent composition was prepared in the same manner as in Example 3, and used in the polishing test of Example 11. Table 3 shows the results of the polishing test using the polishing agent composition of Example 11.
[0096] 4.12 Preparation of the Abrasive Composition of Example 12 A polishing agent composition was prepared in the same manner as in Example 4, and used in the polishing test of Example 12. Table 3 shows the results of the polishing test using the polishing agent composition of Example 12.
[0097] 4.13 Preparation of the Abrasive Composition of Example 13 A polishing agent composition was prepared in the same manner as in Example 5, and used in the polishing test of Example 13. Table 3 shows the results of the polishing test using the polishing agent composition of Example 13.
[0098] 4.14 Preparation of Abrasive Composition of Comparative Example 1 The polishing composition of Example 1 was prepared in the same manner as in Example 1 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 1. The results of the polishing test using the polishing composition of Comparative Example 1 are shown in Table 2.
[0099] 4.15 Preparation of Abrasive Composition of Comparative Example 2 The polishing composition of Example 6 was prepared in the same manner as in Example 6 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 2. The results of the polishing test using the polishing composition of Comparative Example 2 are shown in Table 2.
[0100] 4.16 Preparation of Abrasive Composition of Comparative Example 3 The polishing composition of Example 7 was prepared in the same manner as in Example 7 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 3. The results of the polishing test using the polishing composition of Comparative Example 3 are shown in Table 2.
[0101] 4.17 Preparation of Abrasive Composition of Comparative Example 4 The polishing composition of Example 8 was prepared in the same manner as in Example 8 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 4. The results of the polishing test using the polishing composition of Comparative Example 4 are shown in Table 2.
[0102] 4.18 Preparation of Abrasive Composition of Comparative Example 5 The polishing composition of Example 5 was prepared in the same manner as in Example 5 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 5. The results of the polishing test using the polishing composition of Comparative Example 5 are shown in Table 2.
[0103] 4.19 Preparation of Abrasive Composition of Comparative Example 6 In the preparation of the polishing composition of Example 2, except that the water-soluble polymer compound was changed to JP-18 manufactured by Japan Vam & Poval Co., Ltd., the polishing composition of Comparative Example 6 was prepared in the same manner as in Example 2 and used in the polishing test. The results of the polishing test using the polishing composition of Comparative Example 6 are shown in Table 2.
[0104] 4.20 Preparation of Abrasive Composition of Comparative Example 7 The polishing composition of Example 10 was prepared in the same manner as in Example 10 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 7. The results of the polishing test using the polishing composition of Comparative Example 7 are shown in Table 3.
[0105] 4.21 Preparation of Abrasive Composition of Comparative Example 8 The polishing composition of Example 13 was prepared in the same manner as in Example 10 except that no water-soluble polymer compound was used, and was used in a polishing test as a polishing composition of Comparative Example 8. The results of the polishing test using the polishing composition of Comparative Example 8 are shown in Table 3.
[0106] 4.22 Preparation of Abrasive Composition of Comparative Example 9 The polishing composition of Example 10 was prepared in the same manner as in Example 10 except that the water-soluble polymer compound was changed to JP-18, and used in the polishing test as the polishing composition of Comparative Example 9. The results of the polishing test using the polishing composition of Comparative Example 9 are shown in Table 3.
[0107] 5. Alumina particle size The average particle size of alumina used in the present invention is measured using a laser refraction particle size distribution analyzer (SALD2200, manufactured by Shimadzu Corporation). The average particle size of alumina is the average particle size (D50) at which the cumulative particle size distribution from the smaller particle size side based on volume is 50%.
[0108] 6. Grinding conditions Grinding machine single side grinding machine platform diameter 350mm Substrate High refractive index substrate (MR-10) Circular shape with a diameter of 75 mm Low refractive index substrate (CR-39) Square shape with a side of 50 mm Polishing pad SUBA600 without groove Grinding pressure 160g / cm 2 (High refractive index substrate) 200g / cm 2 (Low refractive index substrate) Platform speed 60rpm Grinding time 8min Abrasive flow rate 25ml / min
[0109] 7. Evaluation of polished substrate 7.1 Determination of grinding speed A micrometer (manufactured by Mitutoyo Co., Ltd., with a measurement accuracy of 1 m m) by measuring the thickness of the substrate before and after polishing, and thereby determining the polishing speed ( m m / min). It should be noted that, for the polishing composition of each Example and Comparative Example, three substrates to be polished were polished simultaneously, and therefore the polishing rate is described as an average value of the three substrates.
[0110] 7.2 Evaluation method of the appearance (blur) of the substrate surface after grinding Blurring of the substrate surface after polishing was determined visually based on the following evaluation conditions by irradiating the substrate surface with light from a spotlight (ECO LIGHT, manufactured by Nagata Seisakusho Co., Ltd., 30,000 Lux) and observing the reflection. The determination was made based on the comprehensive determination of the three substrates polished simultaneously.
[0111] 7.3 Fuzzy evaluation conditions ○: No blur △: Partially blurred ×: Blurred on the entire surface
[0112] 7.4 Method for measuring the surface roughness (Ra) of polished substrates The surface roughness (Ra) of the polished substrate was measured using a 3D measurement laser microscope (manufactured by OLYMPUS Corporation). The measurement conditions were as follows: a measurement device (OLS4100, manufactured by OLYMPUS Corporation, measurement magnification: 2160 times) was used, without cut-off, and the measurement area was set to 128 m m×128 m m.
[0113] Table 2 shows the results of polishing a low-refractive-index substrate using the polishing composition of Examples 1 to 13 and Comparative Examples 1 to 9, and Table 3 shows the results of polishing a high-refractive-index substrate.
[0114] [Table 2]
[0115] [Table 3]
[0116] 8. Inspection First, the results of the polishing test of the low refractive index substrate are examined based on Table 2. m m αImprovement in polishing rate was confirmed in Comparative Examples 1 to 4 using a polishing composition containing no water-soluble polymer compound and Examples 1 to 4 and 6 to 8 using a polishing composition containing no water-soluble polymer compound and using the same alumina.
[0117] If described more specifically, Example 6 having the same pH value of the polishing composition exhibited a polishing rate of about 2 times that of Comparative Example 2 having a pH value (25°C) of 2.0. In addition, Example 2 having the same pH value of the polishing composition exhibited a polishing rate of about 1.6 times that of Comparative Example 1 having a pH value (25°C) of 3.5. Furthermore, Example 7 having the same pH value of the polishing composition exhibited a polishing rate of about 1.2 times that of Comparative Example 3 having a pH value (25°C) of 7.5. Furthermore, Example 8 having the same pH value of the polishing composition exhibited a polishing rate of 1.2 times that of Comparative Example 4 having a pH value (25°C) of 10.0.
[0118] It should be noted that the polishing rate of Comparative Example 6, which used the polishing composition obtained by adding commercially available polyvinyl alcohol (degree of saponification = 88%, degree of polymerization = 1800) to the polishing composition of Comparative Example 1, was not improved compared to Comparative Example 1. Regarding the surface roughness of the substrate after polishing, the results of Examples 2 and 6, in which the pH value (25° C.) of the polishing composition was in the acidic region, were better than those of Examples 7 and 8, in which the pH value (25° C.) of the polishing composition was in the neutral to alkaline range.
[0119] The average particle size (D50) is 0.7 m m α Comparative Example 5 using a polishing composition containing no water-soluble polymer and alumina showed a polishing rate about 2.3 times higher than that of Example 5 using a polishing composition containing an oxazoline group-containing polymer and using the same alumina.
[0120] Example 1 shows the polishing test results of polishing compositions containing different contents of water-soluble polymer compounds containing oxazoline groups relative to Example 2. Examples 3 and 4 show the polishing test results of polishing compositions containing water-soluble polymer compounds containing oxazoline groups with different weight average molecular weights relative to Examples 1 and 2.
[0121] Next, the results of the polishing test of the high refractive index substrate are examined based on Table 3. m m α-Comparative Example 7 using an abrasive composition containing alumina and no water-soluble polymer, and Examples 9 to 12 using the same abrasive composition containing an oxazoline group-containing polymer, an improvement in polishing rate was confirmed. More specifically, the polishing rate of Example 10 was improved by about 2.3 times compared with Comparative Example 7 using an abrasive composition containing no water-soluble polymer. On the other hand, the polishing rate of Comparative Example 9 using an abrasive composition in which commercially available polyvinyl alcohol (saponification degree = 88%, polymerization degree = 1800) was added to the abrasive composition of Comparative Example 7 was not improved compared with Comparative Example 7.
[0122] The average particle size (D50) is 0.7 m m α The polishing rate of Comparative Example 8 using a polishing composition containing no water-soluble polymer compound and Example 13 using a polishing composition containing no water-soluble polymer compound and the same alumina was increased to about 2.2 times.
[0123] Example 9 shows the polishing test results of polishing compositions containing different contents of water-soluble polymer compounds containing oxazoline groups relative to Example 10. Examples 11 and 12 show the polishing test results of polishing compositions containing water-soluble polymer compounds containing oxazoline groups with different weight average molecular weights relative to Examples 9 and 10.
[0124] From the above, it can be seen that whether in the polishing of a low refractive index substrate or in the polishing of a high refractive index substrate, the polishing rate is improved while maintaining the surface roughness and appearance of the polished substrate by containing a water-soluble polymer compound containing an oxazoline group in the polishing agent composition.
[0125] Industrial Applicability The polishing agent composition of the present invention contributes to efficient polishing of plastic lenses widely used as eyeglass lenses and the like and to good surface properties.
Claims
1. A polishing compound composition for a plastic lens, characterized in that: Contains aluminum oxide, water-soluble polymer compounds, and water. The water-soluble polymer compound is an oxazoline group-containing water-soluble polymer compound in which an oxazoline group represented by the following chemical formula 1 is bonded to the main chain of the polymer. , In Chemical Formula 1, R1, R2, R3, and R4 are each any one of H, CH3, and CH2CH3.
2. The polishing compound for plastic lens according to claim 1, wherein The water-soluble polymer compound containing an oxazoline group has a structural unit derived from an acrylic monomer and a structural unit derived from an oxazoline group-containing monomer as essential structural units.
3. The polishing compound for plastic lens according to claim 2, wherein The acrylic monomer is at least one selected from the group consisting of acrylamide, methacrylamide, acrylic acid, acrylate, acrylate, methacrylic acid, methacrylate and methacrylate.
4. The polishing compound for plastic lens according to claim 2, wherein The oxazoline-containing monomer is at least one selected from 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
5. The polishing compound for plastic lens according to claim 1, wherein The water-soluble polymer compound containing an oxazoline group is obtained by graft-polymerizing an addition-polymerizable oxazoline with a polyether.
6. The polishing compound for plastic lens according to claim 1, wherein The oxazoline group-containing water-soluble polymer compound is obtained by reacting an amino alcohol with a polymer having a carboxyl group and / or an ester group.
7. The polishing compound for a plastic lens according to any one of claims 1 to 6, wherein The plastic lens polishing compound further contains a dispersant.
8. The polishing compound for a plastic lens according to any one of claims 1 to 6, wherein The plastic lens polishing compound has a pH value of 1.0 to 10.0 at 25°C.
Citation Information
Patent Citations
Slurry composition and polishing method for organic polymer ophthalmic substrate
JP2008537704A
Slurry composition and method for polishing an organic polymer-based ophthalmic substrate, and an ophthalmic lens
JP2018533071A
Compositions for polishing synthetic resin
US4225349A